Line Patterns from Cylinder‐Forming Photocleavable Block Copolymers. (19th July 2013) - Gu, Weiyin; Zhao, Hui; Wei, Qingshuo; Coughlin, E. Bryan; Theato, Patrick; Russell, Thomas P.
<x xml:space="preserve">Abstract</x> A robust route for the preparation of nanoscopic line patterns from polystyrene‐block‐poly(ethylene oxide) featuring a photocleavable o‐nitrobenzyl ester junction is demonstrated. After mild UV (λ = 365 nm) exposure and selective removal of the PEO microdomains, the polymer trench patterns are used as scaffold to fabricate highly ordered arrays of silica or Au line patterns. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>